How much should i eat? understanding food portion - Learning seed (Lake Zurich, IL : Learning Seed, 2007)
We live in a super-sized world. Our perception of what is an appropriate serving of food is distorted. This program helps viewewrs develop'portion awareness' so that they take control of their own nutrition. Learn to replace'super size it' with'intelli-size it'
Title from title screen
Writer and executive producer, Jeffrey Schrank
Narrator, Kristen Udowitz
With English subtitle
Keywords: Nutrition; Food portions